UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN BAWANG MEKAH (Eleutherine americana Merr.) TERHADAP GAMBARAN HISTOPATOLOGI PARU TIKUS (Rattus norvegicus) WISTAR JANTAN PASCA PAPARAN ASAP ROKOK - Hafidzah Ramadhaniyah Al Idrus; Iswahyudi Iswahyudi; Sri Wahdaningsih (Jurnal Fitofarmaka Indonesia, 2014)
Exposure to cigarette smoke is one of the exogenous free radicals. Exposure to cigarette smoke is associated with lung inflammation, oxidative stress and lipid peroxidation. Compounds that can inhibit the oxidation reaction by binding free radicals known as antioxidants. Eleutherine americana Merr. leaves has an antioxidant activity in invitro study. The aim of this work was to study E.americana leaves as a natural antioxidant that reduce the level of lung damage from exposure to cigarette smoke in male wistar rats and study effective dose of E.americana leaves to reduce the level of lung damage.  The leaves of E.americana extracted by maceration method for 6 days using ethanol 70%. Rats were divided into six groups of four animals each : exposed to ambient air (GroupA), exposed to cigarette smoke (Group B), exposed to cigarette smoke and treated with ethanol extract of E.americana leaves at dose 45mg/kg bw, 90mg/kg bw, 180mg/kg bw (Group C,D,E), exposed to cigarette smoke and treated with vitamin E dose 18mg/kg bb(Group F). All rats were treated for 14 days using 3 cigarettes non filtered each day by using a smoking chamber. After 14 days rats were killed. Right lungs were removed for histopathology. The results showed that dose 45mg/kg bw, 90mg/kg bw, 180mg/kg bw can reduce the level of lung damage to the enlarge of alveolar, thickening of the alveolar wall and inflammatory cell infiltration. Dose 180mg/kg bw as an effective dose to reduce the level of lung damage that compare to normal control.